Structure and magnetism of 4H-BaMnO3-x (0 <= x <= 0.35) and 4H-Ba0.5Sr0.5MnO3-x (0 <= x <= 0.21) - Adkin, J; Hayward, M (2006)
The synthesis and structure determination of 4H-BaMnO3-x (0≤x≤0.35) and 4H-Ba0.5Sr0.5MnO 3-x (0≤x≤0.21) is described. Neutron powder diffraction data unambiguously show the anion vacancies in the oxygen-deficient phases lie in the hexagonal BaO3-x layers, rather than the cubic layers predicted by previous structural models. The localization of anion vacancies in the hexagonal layers is discussed on the basis of the local co-ordination polyhedra of the metal cations. Low-temperature neutron diffraction data show the oxidized materials adopt antiferromagnetic ordered structures (Ba0.5Sr0.5MnO2.99: TN=265K). Anion-deficient phases do not achieve magnetic order suggesting the Mn(III/IV) charge disorder suppresses long-range magnetic order. © 2005 Elsevier Inc. All rights reserved.